Peritoneal dialysis vintage and glucose exposure but not peritonitis episodes drive peritoneal membrane transformation during the first years of PD - Bartosova, Maria; Schäfer, Betti; Vondrak, Karel; Sallay, Peter; Taylan, Christina; Cerkauskiene, Rimante; Dzierzega, Maria; Milosevski-Lomic, Gordana; Büscher, Rainer; Zaloszyc, Ariane; Romero, Philipp; Lasitschka, Felix; et al. (Frontiers in physiology, 2019)
The impact of peritoneal dialysis (PD) associated peritonitis on peritoneal membrane integrity is incompletely understood. Children are particularly suited to address this question, since they are largely devoid of preexisting tissue damage and life-style related alterations. Within the International Peritoneal Biobank, 85 standardized parietal peritoneal tissue samples were obtained from 82 children on neutral pH PD fluids with low glucose degradation product (GDP) content. 37 patients had a history of peritonitis and 16 of the 37 had two or more episodes. Time interval between tissue sampling and the last peritonitis episode was 9 (4, 36) weeks. Tissue specimen underwent digital imaging and molecular analyses. Patients with and without peritonitis were on PD for 21.0 (12.0, 36.0) months and 12.8 (7.3, 27.0) months (p=0.053), respectively. They did not differ in anthropometric or histomorphometric parameters (mesothelial coverage, submesothelial fibrosis, blood and lymphatic vascularization, leucocyte, macrophage and activated fibroblast counts, epithelial-mesenchymal transition (EMT), podoplanin positivity and vasculopathy). VEGF and TGF-ß induced pSMAD abundance were similar. Similar findings were also obtained after matching for age and PD vintage and a subgroup analysis according to time since last peritonitis (6 months). In patients with more than 24 months of PD vintage, submesothelial thickness, vessel number per mmm section length and ASMA fibroblast positivity were higher in patients with peritonitis history; only the difference in ASMA positivity persisted in multivariable analyses. While PD duration and EMT were independently associated with submesothelial thickness, and glucose exposure and EMT with peritoneal vessel density in the combined groups, submesothelial thickness was independently associated with EMT in the peritonitis free patients, and with duration of PD in patients with previous peritonitis. This detailed analysis of the peritoneal membrane in pediatric patients on PD with neutral pH, low GDP fluids, does not support the notion of a consistent long-term impact of peritonitis episodes on peritoneal membrane ultrastructure, on inflammatory and fibrotic cell activity and EMT. Peritoneal alterations are mainly driven by PD duration, dialytic glucose exposure and associated EMT.
Gesehen am 27.08.2019